Association Between Fatty Acids of Blood Cell Membranes and Incidence of Coronary Heart Disease: A Case-Control Study Nested in the PREDIMED Trial. Issue 4 (April 2019) - Papandreou, Christopher; Sala-Vila, Aleix; Galié, Serena; Muralidharan, Jananee; Estruch, Ramón; Fitó, Montserrat; Razquin, Cristina; Corella, Dolores; Ros, Emilio; Timiraos, Juan; Lapetra, Jose; Serra-Majem, Lluis; et al.
Abstract : Objective—: To examine the associations between baseline levels of fatty acids in blood cell membranes and their 1-year changes with the incidence of coronary heart disease (CHD) in older adults at high cardiovascular disease risk. Approach and Results—: This is a case-control study nested in the PREDIMED trial (Prevención con Dieta Mediterránea), with 136 CHD cases and 272 controls (matched on age, sex, body mass index, intervention group, and time of permanence in the study to the time event). We used gas chromatography to measure the proportion of 22 fatty acids in blood cell membranes at baseline and after 1 year. Conditional logistic regression was used to estimate odds ratios (ORs) and 95% CIs. After adjustment for classical CHD risk factors and multiple testing, 1 SD increase in baseline levels of C22:0, C24:0 and the sum of individual very long chain saturated fatty acids was associated with 56% (OR, 0.44 [95% CI, 0.28–0.69]), 59% (OR, 0.41 [95% CI, 0.25–0.65]), and 55% (OR, 0.45 [95% CI, 0.29–0.70]) a decreased odds of developing CHD, respectively. Baseline C20:1n9 was associated with higher odds of CHD (OR, 1.58 [95% CI, 1.25–2.00]). Conclusions—: Higher levels of C22:0 and C24:0 were associated with a lower CHD incidence, whereas higher levels of C20:1n9 were associated with a higher risk. This study adds to the growing body of evidence suggesting potential differences in the cardiovascular disease effects of different types of circulating saturated fatty acids. Abstract : Supplemental Digital Content is available in the text.